Beyond the Mirror: Building Body Trust & Media Literacy - Koski, Peyton (My University, 2025)
The prevalence of eating disorders (EDs) has increased drastically over the past decade, with social media playing a significant role in their development and ongoing perpetuation. This grant proposal not only examines the rising rates of EDs and the underlying factors contributing to their increase, but also highlights the disparities experienced by different communities and identities. Interviews with individuals who have lived experience with EDs, along with a review of current interventions and resources, were conducted to identify the most necessary intervention. The review reveals significant gaps in existing resources, which are primarily based outside the U.S., often costly, lacking in comprehensiveness and gender inclusivity, and focused more on prevention than on providing support for individuals currently struggling with EDs. Clearly, there is a need for an accessible, inclusive intervention that addresses the multiple factors that contribute to negative body image and disordered eating. My proposed intervention, Beyond the Mirror: Building Body Trust and Media Literacy, is a free online program designed for individuals with EDs or body dissatisfaction of all genders, identities, shapes, and sizes. Beyond the Mirror will offer interactive learning modules on Body Trust and media literacy, as well as an optional peer support group. Beyond the Mirror is built on the Body Trust framework and the Developmental Theory of Embodiment (DTE), guiding the program's approach to challenge harmful societal narratives surrounding weight, health, and beauty. Ultimately, this program will empower individuals to cultivate a healthier relationship with their bodies, while also equipping them with the tools to navigate social media in a way that fosters self-acceptance and resilience against unrealistic beauty standards.
Master of Social Work (MSW)
Keywords: Eating disorders; body image; body dissatisfaction; body trust; media literacy